2014
DOI: 10.15288/jsad.2014.75.438
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Pretreatment Commitment to Abstinence: Results from the COMBINE Study

Abstract: ABSTRACT. Objective: Patients entering treatment for alcohol problems do not have uniform treatment goals, and a pretreatment drinking goal has a signifi cant impact on treatment outcome. The objective of this study was to understand better how an array of individual characteristics, including factors that affect treatment, are related to treatment goals before beginning alcohol treatment in the COMBINE (Combining Medications and Behavioral Interventions) Study. Method: Participants were alcohol-dependent indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 43 publications
0
24
1
2
Order By: Relevance
“…In particular, some individuals with high self-efficacy and low physical dependence wish to reduce the high risks associated with heavy drinking, but wish to continue to drink moderately and avoid treatment programs that require abstinence (Marlatt and Witkiewitz, 2002). Indeed, studies have shown that preference for controlled-drinking treatment goals over abstinence range between 25.95% to 86.9% of treatment seekers (e.g., DeMartini et al, 2014; Engasser et al, 2015; Heather et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…In particular, some individuals with high self-efficacy and low physical dependence wish to reduce the high risks associated with heavy drinking, but wish to continue to drink moderately and avoid treatment programs that require abstinence (Marlatt and Witkiewitz, 2002). Indeed, studies have shown that preference for controlled-drinking treatment goals over abstinence range between 25.95% to 86.9% of treatment seekers (e.g., DeMartini et al, 2014; Engasser et al, 2015; Heather et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…5 Since 2000, the prevalence of binge drinking and alcohol disorders increased 28% and 49% in the U.S., 3 but few with alcohol use disorders in the U.S. or Europe receive treatment. 2,3,6,7 Treatments commonly aim for abstinence, 8 but many individuals with alcohol disorders do not accept abstinence goals, 9 at least initially, so drinking-reduction treatments or clinical recommendations may broaden appeal. 10 Further, in addition to psychosocial interventions, medications may broaden interest in treatment by expanding available options.…”
Section: Introductionmentioning
confidence: 99%
“…Once again, the lack of standardized methods among clinical trials and between human laboratory studies and clinical trials hinders the translation from human laboratory findings to clinical outcomes. First, although there tends to be less heterogeneity regarding drinking status and treatment-seeking status in clinical trial participants, there are marked differences in AD phenotype and treatment goals that have been shown to alter the effect of medication (Bujarski et al, 2013;DeMartini et al, 2014). For instance, analyses of the COMBINE Study found that a goal of complete abstinence was associated with an increase in percent days abstinent, days to relapse to heavy drinking, and global clinical outcome compared with a goal of conditional abstinence or controlled drinking (Bujarski et al, 2013).…”
Section: Clinical Trialsmentioning
confidence: 99%